Biological activities study of Cinnamon (Cinnamomum burmanni (Nees & T.Nees) Blume) as Cosmetic Ingredients - Rizaldy, Defri; Insanu, Muhamad; Hartati, Rika; Fadhilah, Ismah Ibtihal; Putri, Rian Destiyani; Cheong, Min Kyoung (School of Pharmacy Institut Teknologi Bandung, 2024)
Objectives: The goals of this research were to study the biological activities of cinnamon bark extract related to its use as cosmetic ingredients. The potential use of cinnamon bark as cosmetic preparations was studied by confirming its antioxidative, antimicrobial, and its inhibition towards tyrosinase activity. Methods: Extraction was performed by maceration using 70% ethanol. Antioxidative activity using the DPPH methods, melanin inhibitory effect was determined using in vitro anti tyrosinase assay. MHC and MIC of cinnamon bark extract were determined towards Staphylococcus aureus, Staphylococcus epidermidis, and Cutibacterium acnes. Results: The standardization result of the crude drugs showed positive result on qualitative analysis of Flavonoid, Tannin, and Quinone groups. Flavonoid content also found on the ethanolic extract. The IC50 antioxidative activity of cinnamon ethanolic was 7.52 ± 0.13 μg/mL compared to ascorbic acid with 2.54 + 0.02 μg/mL. The Ethanolic extract of cinnamon inhibited tyrosinase with IC50 of 9.44 ± 0.26 mg/mL. Lowest minimum inhibitory concentration of ethanolic extract was found towards Cutibacterium acne with 1000 μg/mL. Whereas weak antimicrobial activity was showed towards Staphylococcus aureus and Staphylococcus epidermidis with MIC and MBC value started from 2000 μg/mL. Conclusion: Comparable result on antioxidative and anti-tyrosinase analysis shows that cinnamon bark have fair potential to further developed and formulated for topical maintenance product.